The puzzling genus Xenomyia Malloch (Diptera, Muscidae): taxonomic notes, key to species and redescription of Xenomyia hirtibasis (Bigot) - Couri, Márcia Souto; Sousa, Viviane Rodrigues De; Gomes, Marina; Gil-Azevedo, Leonardo H. (Zootaxa, 2025)
Xenomyia Malloch (Diptera, Muscidae) is a very interesting genus that includes predacious species with unusual combinations of characters. It is exclusively found in the Afrotropical region and currently comprises 16 species. The recent collection of the species Xenomyia hirtibasis (Bigot) in South Africa, has prompted this study, in which the species is redescribed, including, for the first time, the morphology of male and female terminalia, until now known only for Xenomyia natalensis Zielke (cercal plate and surstyli) and Xenomyia osculata Pont & Werner (male and female). Additionally, a key for the identification of all 16 species is provided, along with diagnoses for each species. Besides the original illustrations, we have gathered all available illustrations of the species from the literature, to facilitate the identification of them. Finally, we provide a map with the known geographical distribution of the species.